Regulating the reactivity of black phosphorus via protective chemistry - Liu, Xiao (2021)
Rationally regulating the reactivity of molecules or functional groups is common in organic chemistry, both in laboratory and industry synthesis. This concept can be applied to inorganic nanomaterials, particularly two-dimensional black phosphorus (BP) nanosheets. The high reactivity of few-layer (even monolayer) BP is expected to be "shut down" when not required and to be resumed upon application. Here, we demonstrate a protective chemistry-based methodology for regulating BP reactivity. The protective step initiates from binding Al3+ with lone pair electrons from P to decrease the electron density on the BP surface, and ends with an oxygen/water-resistant layer through the self-assembly of hydrophobic 1,2-benzenedithiol (BDT) on BP/Al3+ This protective step yields a stabilized BP with low reactivity. Deprotection of the obtained BP/Al3+/BDT is achieved by chelator treatment, which removes Al3+ and BDT from the BP surface. The deprotective process recovers the electron density of BP and thus restores the reactivity of BP.